The robust curve-fitting based method for coordinated voltage regulation with distributed generator and OLTC in distribution network - Tuncel, Suleyman; Gözel, Tuba (Elsevier, 2023)
The voltage violation in distribution networks may occur frequently due to the rising integration of flexible demands and supplies. In this paper, the reactive power of the inverter -based distributed generator (DG) and OLTC tap position are adjusted for voltage regulation in coordinated manner. Firstly, the reactive power adjustment for the voltage regulation has been car-ried out by use of the DG reactive power capacity. Afterwards, the tap position of the OLTC has been changed to regulate the bus voltage that has a voltage violation problem in the case of insuf-ficient reactive power capacity of the DG inverter. The value of the distributed generator reactive power output that regulates the voltage on the bus that has a voltage violation is found with pro-posed curve-fitting method and tested with the Grid Search, Artificial Bee Colony methods. The proposed method derives mathematical expressions between DG reactive power output and bus voltages as quadratic equations by curve-fitting technique. Moreover, addition to inherent upper and lower reactive power limits of the DG inverter, they are determined by the proposed curve -fitting based technique while considering voltage constraints on all buses. Proposed method is much faster than other two methods because of its plain structure and gives adequate accurate results.& COPY; 2023 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/ licenses/by-nc-nd/4.0/).
Keywords: Voltage regulation; Distributed generator; VAr-Volt control; Curve -fitting; Reactive power adjustment; OLTC